Apoptosis and frequency of total and effector CD8+ T lymphocytes from cutaneous leishmaniasis patients during antimonial therapy - Ferraz, Raquel (2015)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Laboratório de Imunoparasitologia. Rio de Janeiro, RJ, Brasil / Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Plataforma de Citometria de Fluxo – Purificação celular. Rio de Janeiro, RJ, Brasil.